2013
DOI: 10.1007/s00405-013-2466-4
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal trigeminal sensitivity: measurements before and after nasal surgery

Abstract: Nasal surgeries constitute an extensive manipulation of the nasal mucosa and therefore of structures related to trigeminal and olfactory sensitivity. While olfactory changes due to nasal surgery are relatively well investigated, there are only very few studies regarding trigeminal sensitivity. Aim of the present study was to investigate sensory changes after nasal surgery with special regard to the trigeminal sensitivity. In 38 patients prior to and around 12 weeks after nasal surgery the following psychophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
3
19
0
2
Order By: Relevance
“…The comparison between patients having concomitant septoplasty or not showed no difference in trigeminal function and subjective patency perception. Scheibe et al studied the trigeminal function of patients before and after septoplasty and found a decreased trigeminal sensitivity in patients before surgery . In the same study, septal surgery had no effect to the trigeminal sensitivity, a fact that is in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison between patients having concomitant septoplasty or not showed no difference in trigeminal function and subjective patency perception. Scheibe et al studied the trigeminal function of patients before and after septoplasty and found a decreased trigeminal sensitivity in patients before surgery . In the same study, septal surgery had no effect to the trigeminal sensitivity, a fact that is in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increased patency perception could be achieved through mucosal heat loss/ cooling (7,8) . Further, a higher trige-minal detection threshold in patients undergoing septoplasty compared to healthy subjects revealed the important role of endonasal trigeminal sensitivity in patients with nasal breathing difficulties scheduled for surgery (9) .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is empirical evidence suggesting that trigeminal sensitivity does not improve with surgical interventions such as sinus surgery [21]. In fact, a subjectively congested nose may not exclusively have an anatomical origin but might also result from insensitivity of the nasal trigeminal nerve.…”
Section: Introductionmentioning
confidence: 99%